The impact of cardiovascular comorbidities associated with risk for left heart disease on idiopathic pulmonary arterial hypertension: Data from the Hellenic Pulmonary Hypertension Registry (HOPE). (7th June 2022) - Arvanitaki, Alexandra; Vrana, Elena; Boutsikou, Maria; Anthi, Anastasia; Apostolopoulou, Sotiria; Avgeropoulou, Aikaterini; Demerouti, Eftychia; Patrianakos, Alexandros; Karyofyllis, Panagiotis; Mitrouska, Ioanna; Mouratoglou, Sophia A.; Naka, Katerina K.; et al.
Abstract: Whereas younger female patients were diagnosed with idiopathic pulmonary arterial hypertension (IPAH) in 1980s, it is now frequently encountered in elderly patients with cardiovascular comorbidities (CVCs) associated with increased risk for left heart disease. We present data until November 2019 regarding specific features and clinical outcomes of IPAH population from the Hellenic Pulmonary Hypertension Registry (HOPE). Patients were divided into two groups based on the presence of ≥ or <3 CVCs, arterial hypertension, diabetes mellitus, obesity, presence of coronary artery disease, or atrial fibrillation. Overall, 77 patients with IPAH (55.1 [interquartile range, IQR: 24.1] years, 62.8% women) have been recorded. Fifteen patients (19.2%) had ≥3 CVCs, while 25 (32%) were over 65 years old. Patients with ≥3 CVCs were older, presented an almost equal female to male ratio, walked less in 6‐min walk test, and had lower mean arterial pulmonary pressure and pulmonary vascular resistance at baseline than patients with less CVCs. Fewer patients with ≥3 CVCs received PAH‐specific treatment compared to patients with less comorbidities ( n  = 11 [73.3%] versus n  = 58 [95.5%], p  = 0.02). During a median follow‐up period of 3.8 (IQR: 2.7) years, 18 patients died (all‐cause mortality 24.3%). Male sex and older age were independent predictors of mortality and/or lung transplantation, while CVCs did not have a significant impact on clinical outcomes. In this nationwide, register‐based study,  the epidemiology of IPAH involves older patients with CVCs, who seem to have less hemodynamic compromise, but worse functional impairment and are treated less aggressively with PAH pharmacotherapy.